Comparative European party systems : an analysis of parliamentary elections since 1945 - Siaroff, Alan (Garland reference library of social science, 2000)
This book provides a comprehensive analysis of the party systems of the whole continent of Europe. This work also includes case studies of the Baltic States and Balkan democracies and goes as far east as Russia, Ukraine, Georgia, and Turkey.